(untitled) (Journal of Rangpur Medical College, 2025)
Background: Dengue fever remains a major global health concern, particularly in pediatric populations in endemic countries like Bangladesh. Objective: This study aimed to evaluate the prevalence of prolonged and saddleback fever patterns and their association with clinical severity and outcomes among pediatric dengue patients. Methods: This cross-sectional analytical study was conducted in the Pediatric Intensive Care Unit (PICU) of Bangladesh Shishu Hospital and Institute from August 2023 to February 2025. A total of 47 pediatric dengue patients under <18 years with confirmed infection (NS1 or IgM positive) were analyzed. Fever patterns were categorized as prolonged or biphasic (saddleback). Patients without prolonged or saddle-back fever were considered controls. Clinical presentations, laboratory parameters, complications, and outcomes were documented. Logistic and linear regression analyses were conducted to determine the association between fever pattern and disease severity. Results: Prolonged and saddleback fever groups demonstrated significantly higher complications, including hepatic involvement (OR=2.50, p=0.04) and co-infections (OR=4.21, p=0.03). Both groups exhibited pronounced thrombocytopenia (platelets <50,000/μL), hematocrit elevations (>20%), and severe coagulopathy compared to controls. Mortality was notably higher in prolonged fever (18.2%) and saddleback fever (16.7%) groups versus controls (3.3%). Logistic regression revealed prolonged fever significantly reduced the odds of clinical improvement (OR=0.13, p=0.03), while saddleback fever showed a borderline significant reduction (OR=0.22, p=0.05). Male sex (OR=1.65, p=0.05) and older age (OR=1.22, p=0.002) increased the likelihood of prolonged or saddleback fever. Conclusion: Prolonged and saddleback fever trajectories in pediatric dengue patients are associated with heightened clinical severity, increased complication risks and reduced survival. Recognition of these fever patterns could enhance early clinical risk stratification, guiding management and optimizing outcomes in pediatric dengue, particularly in resourcelimited endemic regions. J Rang Med Col. 2025 Sep;10(2): 128-134